1993
DOI: 10.3109/00365529309096073
|View full text |Cite
|
Sign up to set email alerts
|

Regional Small-Intestinal Permeability in Vitro to Different-Sized Dextrans and Proteins in the Rat

Abstract: Molecular weight-dependent passage over different regions of the rat small intestine, using different-sized proteins/peptides and fluorescein isothiocyanate-dextrans in the 1- to 70-kDa range, was studied in vitro in modified Ussing chambers. The mucosal to serosal passage was inversely related to the molecular weight. After 120 min the passage in the proximal region usually dominated, but the nonapeptide (mercaptopropionic acid1, D-arginine8)-vasopressin differed by showing a consistently higher passage in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 31 publications
5
39
1
Order By: Relevance
“…Disruption of the mucosal barrier, or the movement of microand macromolecules from the lumen to the circulation across enterocytes, has been reported under various conditions [22]. Minimal but similar movement of the marker substance through the enteric mucosa of the normal dog was demonstrated in this study, as described in the normal rat intestine [23]. Pantzar et al, using the same Ussing chamber technique, demonstrated that 0.03-0.04% of the FITC-conjugated Dextran injected into the mucosal-side reservoir was recovered from the serosal-side solution after 60 min perfusion.…”
Section: Discussionsupporting
confidence: 48%
“…Disruption of the mucosal barrier, or the movement of microand macromolecules from the lumen to the circulation across enterocytes, has been reported under various conditions [22]. Minimal but similar movement of the marker substance through the enteric mucosa of the normal dog was demonstrated in this study, as described in the normal rat intestine [23]. Pantzar et al, using the same Ussing chamber technique, demonstrated that 0.03-0.04% of the FITC-conjugated Dextran injected into the mucosal-side reservoir was recovered from the serosal-side solution after 60 min perfusion.…”
Section: Discussionsupporting
confidence: 48%
“…where c i represents the concentration of the marker molecule present in the serosal half-cell (M) and c 0 represents the initial concentration of the same marker molecule in the mucosal half-cell (M) (18) . The apparent permeability coefficient (P app ) was calculated for the macromolecules FITC-dextran and ovalbumin by means of the formula:…”
Section: Calculationsmentioning
confidence: 99%
“…where dc/dt represents the change of serosal concentration in the 60 to 120 min period (M/s), V the volume in the half-cells (cm 3 ), c 0 the initial marker concentration in the mucosal half-cell (M), and A the area of exposed intestine in the Ussing chamber (cm 2 ) (18) .…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin absorption appears to differ between intestinal regions because the protease content is much higher in the upper small intestine than in the descending small intestine (24). Furthermore, the permeability of macromolecular drugs is molecular weight-dependent passage over different regions of the small intestine (25). Therefore, the design of an optimal oral delivery system of insulin using a physical complex of CPPs depends on understanding the different effects of CPPs on the insulin absorption along the intestinal tract.…”
Section: Introductionmentioning
confidence: 99%